A Flexible Risk-Based Security Evaluation Methodology for Information Communication Technology System Certification - Sara N. Matheu; Juan F. Martínez-Gil; Irene Bicchierai; Jan Marchel; Radosław Piliszek; Antonio Skarmeta (Applied Sciences)
As Information and Communication Technology (ICT) systems become increasingly complex, the need for adaptable and efficient security certification frameworks grows. This paper introduces a flexible security evaluation methodology designed to serve as the foundation for cybersecurity certification across diverse ICT systems. The proposed methodology integrates risk assessment and test-based evaluation, offering a scalable approach that adapts to different tools and processes, addressing the limitations of existing rigid certification schemes. The certification approach expands on ETSI’s Risk-Based Security Assessment and Testing methods, based on ISO 31000 and ISO 29119, and it integrates widely recognized standards such as MUD. This ensures an objective, empirical evaluation process that enables partial automation and simplifies recertification. As a proof of concept, we validate the methodology in two real use cases, an ICT gateway for smart grids and an AI-powered investments platform, demonstrating its flexibility and applicability to real-world contexts while addressing the challenges of modern ICT ecosystems.